Fundamentals of Enterprenuership (ENT300) Business Model Canvas (BMC) : Kukista / Siti Nurmaisarah Mohd Hairuddin - Mohd Hairuddin, Siti Nurmaisarah (2020)
Kukista is a handmade biscuit by me myself, Siti Nurmaisarah Binti Mohd Hairuddin. The name Kukista comes from the cookies word itself, while the ‘ta’ referred to the word ‘kita’. Since I love to eat cookies so much, I was withdrawn to make them myself, to enjoy it anytime I want. Thus, I prefer to share the excitement in eating and enjoying cookies in everyday life. The easiest and fastest way that I can think of is opening a small cafe under my own brand name. I decided to come out with Kukista in this coming May 2020. Therefore, I fully utilized my two-month period of semester break to prepare for the cafe opening such as registering for SSM and LHDN.